Aggressive conservative versus surgical management of lumbar spine problems in elite tennis players - Hainline, B. (1997)
Low back pain is a common problem in elite tennis players. In 1995, injury to the low back was the most common reason for player withdrawal at ATP Tour events. Epidemiologic data demonstrate that at the elite level, the majority of musculoskeletal injuries occur in the lower extremities and lumbar spine. This contrasts with the average club tennis player, in whom the majority of injuries occur in the upper body. Surprisingly, despite the high incidence and prevalence of lumbar spine injuries, the majority of players are either ignorant of or neglect trunk musculature in their training. This is compounded by the fact that the majority of musculoskeletal injuries to elite tennis players are a result of overuse injuries, and proper rehabilitation as a whole is often lacking.There are virtually no data regarding a relation-ship between lumbar spine injury, trunk strength, training techniques and musculoskeletal injuries in general. Specific recommendations: It is difficult to make specific recommendations regarding proper management of lumbar spine injuries in elite tennis players when data are so incomplete. With the advent of a more comprehensive database in both the Corel WTA Tour and the ATP Tour, and through clinical and scientific conferences devoted to tennis, management issues should become more scientific in the future. Surgical management of lumbar spine problems in elite tennis players is rarely needed. Therefore, we can focus on aggressive conservative management. Regarding general guidelines, the first rule of thumb is that trunk injuries must be viewed within a kinetic chain. Although hard data are lacking, personal experience indicates that trunk injuries often occur in a continuum with prior lower and upper extremity injuries, coupled with incomplete rehabilitation. The majority of tennis players can be properly rehabilitated through a careful and well thought-out long-term rehabilitation programme which focuses on the kinetic chain, lumbar stabilization and overall musculoskeletal balance.